Development of the modified high Cr ferritic heat-resistant steel. (November 2015) - Liu, C. X.; Liu, Y. C.; Ning, B. Q.
Abstract : High Cr ferritic heat-resistant steels have been the important structural materials for elevated temperature application in the advanced power plants. Owing to the severe difficulties encountered by energy shortage and environment pollution, it is imperative to improve the serving temperature up to 650° which would largely elevate the thermal efficiency of generating station. In this paper, the phase transformation behaviours, strengthening mechanism and the formation the precipitates of high Cr ferritic steels were summarised. Based on these, the modified high Cr ferritic steel for 650 °C condition was developed by our group. The tensile and creep tests indicate that the modified steel has the outstanding mechanical properties, suggesting it may be the candidate materials in advanced power plants for 650 °C grade. Furthermore, developments of the modified high Cr ferritic steels will be presented and discussed in views of microstructural control, alloy design, phase transformation behaviours and high-temperature performance.